Perbandingan Kriptografi Klasik Hill Cipher dengan Affine Cipher dalam Pengamanan Data Citra - I Nyoman Dwi Pradnyana Putra; I Gede Santi Astawa (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
The development of technology affects several aspects of life, especially in securing confidential data and information. Because of this, there is a way to secure data, namely cryptography, many cryptography techniques have been implemented to hide data information, one of which image data, the purpose of securing image data is to prevent unwanted things such as fraud by using other people’s identities supported by personal photos. In this research, two classical cryptography algorithms will be tested, namely hill cipher and affine cipher by comparing the MSE and PSNR Image values when encryption is carried out. The encryption process is done 6 times with different image in each algorithm, the results of the encryption are compared between the results of the hill cipher encryption image with the affine cipher